Ham Sok Hon: Bridging Spirituality and Politics - Song-Chong Lee (Religions, 2024)
This paper aims to offer an interpretation of Ham Sok Hon’s views on the dynamic relationship between religion and politics. While considerable discussion has already taken place in the Korean academic community across various fields, including philosophy, theology, and political science, many of which propose ssial philosophy as the metaphysical foundation of his political thoughts, there still remains a need for a more systematic understanding of their relationship, which I argue is closely linked to his concept of jeonilhwa gwajeong (the process of unification/integration). By exploring Ham’s unique analysis, particularly in relation to the notion of ipcheseong (stereoscopic/multi-dimensional), this paper will underscore their shared roots and objectives across different spheres of life: one pertaining to salim (human affairs) seeking the pursuit of fairness and equality, and the other dealing with spirituality, aspiring to grasp the sublime aspects of human existence. Both religion and politics, as these movements are termed, are mutually dependent, with their culmination promising peace and harmony in historical reality. Through highlighting Ham’s integrated perspective on religion and politics, I will ultimately suggest a specific discourse—civil religion—as a theoretical framework to effectively unravels Ham’s viewpoints.